Large Carpenter Bees as Agricultural Pollinators - Tamar Keasar (Psyche: A Journal of Entomology)
Large carpenter bees (genus Xylocopa) are wood-nesting generalist pollinators of broad geographical distribution that exhibit varying levels of sociality. Their foraging is characterized by a wide range of food plants, long season of activity, tolerance of high temperatures, and activity under low illumination levels. These traits make them attractive candidates for agricultural pollination in hot climates, particularly in greenhouses, and of night-blooming crops. Carpenter bees have demonstrated efficient pollination service in passionflower, blueberries, greenhouse tomatoes and greenhouse melons. Current challenges to the commercialization of these attempts lie in the difficulties of mass-rearing Xylocopa, and in the high levels of nectar robbing exhibited by the bees.